2006
DOI: 10.1063/1.2141950
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical elastic cross sections for electron collisions with the C3H6 isomers

Abstract: In the present work we report cross sections for electron collisions with the isomers propene (C3H6) and cyclopropane (c-C3H6). Electron-scattering differential cross sections (DCS) are reported for measurements carried out for energies 1.5-100 eV and the angular range of 20 degrees-120 degrees. Elastic integral cross sections (ECS), DCS, and momentum-transfer cross sections (MTCS) are reported for calculations carried out using the Schwinger multichannel method with pseudopotentials for the energy range of 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 39 publications
2
13
0
Order By: Relevance
“…(2). We find satisfactory agreement both for the integral elastic cross section plotted as a function of electron energy shown in 39 and squares, 40 while circles represent the previously reported total cross section. 41 Present experimental data are denoted by diamonds.…”
Section: A Elastic Cross Sectionssupporting
confidence: 57%
See 2 more Smart Citations
“…(2). We find satisfactory agreement both for the integral elastic cross section plotted as a function of electron energy shown in 39 and squares, 40 while circles represent the previously reported total cross section. 41 Present experimental data are denoted by diamonds.…”
Section: A Elastic Cross Sectionssupporting
confidence: 57%
“…The present experimental data are shown with the black line, while the previous measurements are denoted by squares. 40 The red line shows present calculations, blue line displays results of previous Schwinger multi-channel calculations, 40 and the green line represents single-center expansion calculations. 42 may be assigned to the use of a single (electronic) channel model.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…The isomer effect allows one to distinguish between different isomers of a given molecule by differences in the scattering cross sections (total, integral elastic, differentials, rotation excitation). We investigated isomers of the hydrocarbons C 3 H 4 , C 4 H 6 , C 4 H 8 , C 4 H 10 and C 3 H 6 [74][75][76][77][78][79]. The results for energies between 10 eV and 40 eV, suggested that the integral cross sections for the isomeric group differed by a factor that could be obtained through a scaling law based on geometrical optics (in fact this is a general model that was applied for molecules other than hydrocarbons) [80].…”
Section: Elastic Scattering: Single Open Channelmentioning
confidence: 99%
“…Both molecules have been intensively studied experimentally (Allan 1994, Allan and Andric 1996, Szmytkowski et al 2002a, Makochekanwa et al 2006, Boesten et al 1994, Tanaka et al 1999. While number of theoretical calculations is thorough for the cyclopropane molecule (Winstead et al 1992, Beyer et al 1997,Čurík and Gianturco 2002a, Makochekanwa et al 2006, to our knowledge there is only one SE calculation by Winstead et al 1991 for the propane molecule. A visual comparison of the spherical components u 0 0 (r) defined by Eq.…”
Section: Application To Elastic Scattering On Small Hydrocarbonsmentioning
confidence: 99%